Development of Problem-Based Learning (PBL)-Based Digital Books (E-Books): Public Administration at SMK NU Lamongan - Diyah Arum; Siti Sri Wulandari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This study examines the development of an e-book based on the Problem-Based Learning (PBL) approach in public administration learning materials, evaluates its feasibility, and analyzes students’ responses to the developed product. The research employed a Research and Development (R&D) design using the IDI procedural model (Instructional, Development, and Institute), which consists of three main stages: define, develop, and evaluate. The research data included the developed e-book product and quality assessment results obtained through expert validation sheets and student response questionnaires. Product validation was conducted by design experts, material experts, and linguists using a scoring scale of 0–100, while student responses were collected through interviews. The validation results showed that the average score from design experts was 73.25%, indicating that the e-book is valid and feasible. The material experts’ evaluation yielded an average score of 83.12%, categorized as valid and feasible, while linguists provided an average score of 92.25%, indicating a very feasible product. Overall, the combined validation score reached 84.3%, confirming that the e-book is valid and suitable for use. This finding is further supported by student response results, which showed an average score of 93.5%, demonstrating that the developed digital book is highly feasible and well received for learning purposes.